Analysing Muamalat features for a sustainable development of Islamic finance in Uganda: a systematic literature review - Kaweesa, Yusuf; Rosman, Romzie (Universiti Malaysia Sabah, 2025)
Islamic banking and finance have gained wide acceptance in different parts of the world with more than 76 jurisdictions already embracing the industry, with industry reaching USD3 trillion in 2022. Besides, lately, Islamic banking has been introduced in Uganda, and in 2023, the first fully-fledged bank was licensed by the Bank of Uganda. However, society needs to be exposed to the underlying principles guiding Islamic finance. This study uses a systematic literature review to analyse different muamalat principles that guide Islamic banking. This study identified the enhancement of financial and social inclusion in society, the collection and distribution of zakat and sadaqah, the establishment of qard hasan, the conservation of societal values and averting of harm, and the promotion of ethical values and exhibition of quality customer service as Muamalat principles that can aid in informing Ugandans about novel concepts that can clarify the operationalisation of Islamic banking.